Hubungan Penggunaan Ice Breaking Dengan Motivasi Belajar Siswa Dalam Pembelajaran Fiqih di MAN 4 AGAM - Nadia Kasuma; Afrinaldi Afrinaldi; Hamdi Abdul Karim; M. Arif (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The title of this article is "The Relationship between Using Ice Breakers and Students' Learning Motivation in Studying Fiqh at MAN 4 Religions". Compiled by Nadia Kasuma and NIM 2119 118 UIN Sjech M. Djamil Djambek Bukittinggi. 2023. Led by Dr. Afrinaldi, M.A. The aim of this research is to find out whether there is a relationship between the use of ice breakers and the motivation to study Islamic law among MAN 4 Agam students. The author conducted this research because the researcher found several problems in teaching fiqh to Man 4 Agam school students. Where is the problem? Students lose concentration when the teacher explains the material in such a way that learning becomes monotonous and uncomfortable. Apart from that, many students make noise during learning when the teacher is explaining. The type of research used by the author is correlation with quantitative data processing. The sample consisting of classes X MIPA1, X MIPA 2, X IPS1 and X IA was taken as a sample of 93 students. The research instrument is in the form of a survey or questionnaire and processed using Statistical Product and Service Solution (SPSS) version 21. Based on the blood pressure test, there is a significant relationship between the independent variable ice breaker and the dependent variable student learning. ". Motivating". and there is a significant value between the independent variable and (two-sided). 0.009 > 0.005, then there is a significant relationship between the ice breaker variable and student learning motivation. It can be concluded that Ha is accepted and Ho is rejected.